Capturing The PCK Ability of Prospective Science Teachers Using Core and PaP-Er (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
This study involving prospective science teachers at SMP aims to portray the ability of Pedagogical Content Knowledge (PCK) of the teachers via resource folios. Resource folios in question are the core and PaP-eRs made by the prospective science teachers when carrying out the “Program Pengalaman Lapangan” (PPL). The subjects were six candidates conducting PPL at a junior high school and were assigned by the class teachers to teach Grade VII. The instrument used as a means of collecting data in this research is the CoRe and PaP-eRs. The instrument has been analyzed using an analytical format. The result of CoRe and PaP-eRs analysis shows that the learning activities are carried out on the whole in accordance with lesson plans that have been rendered previously. However, the instruction plan is focused more on the CoRe content materials to be studied, while the narrative of learning implementation in the PaP-eRs is emphasized more on learning activities. The results show that the PCK ability of prospective teachers still do not show the integration between content capability and pedagogical ability.